Leptospirosis: predictors of poor outcomes in hospitalized patients, 25 years of experience (Actualizaciones en Sida e Infectología, 2024)
IntroductionLeptospirosis is an emerging zoonotic disease that poses a public health problem. Renal failure, thrombocytopenia, and respiratory involvement have been described as predictors of mortality.ObjectivesTo describe the clinical, radiological, and laboratory characteristics of hospitalized individuals with leptospirosis and evaluate predictors of poor clinical outcomes (PCO).Materials and methodsA prospective cohort study was conducted including patients with leptospirosis admitted to a hospital in the city of Santa Fe between 1997 and 2022. PCO was defined as admission to the Intensive Care Unit (ICU), requirement for mechanical respiratory assistance (MRA), and/or death. The chi-square test, Student's t-test, or Mann-Whitney U test were used as appropriate. A binary logistic regression was performed with variables having p
Keywords: leptospirosis; Leptospira; Weil syndrome; endemic diseases